Memórias Ghibli: A tessitura mnemônica no consumo dos filmes de Isao Takahata e Hayao Miyazaki - Horta , Lilia Nogueira Calcagno (2024)
Ghibli is a Japanese animation studio, founded in 1985 and constantly awarded throughout its history. Since the 90s, it has remained at the top of the Japanese box office rankings and, more recently, has become significantly known throughout the world. It’s films have some peculiar characteristics: long lasting, mostly manuals, complex characters and plots. They mobilize several layers of memory in their creative process, coming from both personal and collective sources. In order to investigate how such layers are articulated, analyzes are carried out on the corpus made up of all the studio's feature films with a focus on the works created by the main directors, Isao Takahata and Hayao Miyazaki. Interviews, ocumentaries, biographies, in addition to an academic bibliographical survey, serve as a basis for theoretical construction, using the pillars of communication and consumption, cinema and animation, Japanese culture and memories through a multidisciplinary theoretical perspective. As specific objectives, we intend to discuss about the construction of anime market, stage for Ghibli creation; analyze Isao Takahata and Hayao Miyazaki aesthetic and constructions, explaining the articulation of memories on their works, observing differences and similarities between the two directors; identify layers of memory linked to the directors works and the studio as a whole, build a methodological framework, delving deeper into each one of the layers. The results demonstrate that layers of memories are vital parts in the composition of the studio's works and in the creative process, even if there are similarities and differences in the approach of different directors.